A Study on Noun Suffixes: Accounting for the Vernacularisation of English in Late Medieval Medical Texts - Crespo, Begoña (Linguistik Online, 2012)
This paper seeks to contribute to the study of the vernacularisation process in late Middle English by measuring up to what an extent concrete and abstract noun suffixes (in line with Dalton-Puffer 1996) attach to either Germanic or Romance bases in the medical texts extracted from the MEMT (Middle English Medical Texts) corpus. The findings obtained have been further described according to text type or genre and to target audience/readership. The description of these suffixes in relation to all the parameters already mentioned has confirmed the predominance of abstract suffixes of Romance origin although Germanic abstract suffixes are also abundant. More hybrid formations have been found with Germanic noun suffixes than with Romance ones which might be indicative of their versatility towards vernacularisation.